Measuring the Strength of Market Preference and Advocacy to Boost Sales in University-Incubated Startups - Ahmad Ikhwan Setiawan; Evan Septhian Batista; Cheryl Marlitta Stefia (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study examines: (1) the influence of product attractiveness and digital promotion innovation on consumer preference; (2) the effect of consumer preference on digital advocacy leverage; and (3) the impact of consumer preference and digital advocacy leverage on marketing performance (sales growth) among university-incubated culinary startups in Indonesia. Research Design & Methods: A purposive sampling technique was applied, yielding 262 respondents. Data were analyzed using Structural Equation Modeling (SEM) with AMOS software. Findings: The results show that product attractiveness and digital promotion innovation significantly strengthen consumer preference. Consumer preference significantly influences both digital advocacy leverage and sales growth, confirming its central role within the Consumer 5A framework. Digital advocacy leverage also positively affects sales growth. However, digital promotion innovation does not directly influence digital advocacy leverage, indicating that advocacy arises from consumer preference and experience rather than promotional novelty alone. Implications & Recommendations: University-incubated culinary startups should: (i) prioritize sensory validation and consistent product and packaging quality to reinforce the Appeal → Preference pathway; (ii) align short-form, personalized, and influencer-supported digital content with the product’s value proposition; and (iii) implement post-advocacy conversion mechanisms—such as review prompts, referral programs, curated user-generated content, and seamless ordering links—to convert advocacy into measurable sales. Contribution & Value Added: This study demonstrates that consumer preference is the key bridge linking product attractiveness and digital promotion to e-advocacy and sales performance, with digital promotion influencing advocacy only indirectly, offering actionable insights for incubator-based startup development.